Phytochemical Analysis of Psidium Guajava Leaf Extracts - Baloch, Mahnoor; Zarlish,; Soomro, Samra; Ujjan, Saher (Indus Journal of Bioscience Research, 2024)
Background: Psidium guajava (guava), a medicinal plant from the Myrtaceae family, has been widely used in traditional medicine for its anti-inflammatory, antimicrobial, and antioxidant properties. The plant is known for its rich phytochemical composition, which supports its therapeutic applications. Objective: This study aimed to analyze the phytochemical profile of Psidium guajava leaves using different solvent extracts to identify bioactive compounds with potential pharmacological benefits. Methods: Guava leaves were collected, shade-dried for 35 days, and ground into a coarse powder. Sequential solvent extractions were performed using ether, chloroform, ethanol, water, and hydroalcoholic solvents. Standard phytochemical tests were applied to detect alkaloids, flavonoids, tannins, saponins, sterols, carbohydrates, and other bioactive compounds. Quantitative data were statistically analyzed using SPSS (version 26). Results: Ethanolic and hydroalcoholic extracts exhibited the highest concentrations of phytochemicals. Alkaloids were strongly present in the ethanolic extract (Dragendorff’s reagent: +++, Hager’s reagent: ++). Tannins showed the highest presence in ethanolic, aqueous, and hydroalcoholic extracts (+++). Flavonoids were consistently detected in polar extracts (++). Carbohydrates were significantly abundant in ethanol, aqueous, and hydroalcoholic extracts (++). Nonpolar extracts (ether, chloroform) yielded minimal phytochemicals. Conclusion: The study confirmed the presence of significant bioactive compounds, particularly in polar extracts, validating the pharmacological potential of guava leaves and their relevance in drug development.